ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 16 ATAS ASSET TETAP PADA PT. PATRA SELARAS SEJATI - Sri Hartati; Rian Sapurta (Bajang Institute, 2023)
Fixed assets have an important role in supporting the company's operational activities and possess material value in the financial statements. Therefore, companies need to apply fixed asset accounting policies in accordance with PSAK No. 16. This study aimed to obtain empirical evidence and analyze the implementation of PSAK No. 16 policy regarding the fixed assets of PT. Selaras Sejati. The research was conducted using qualitative research method with the research approach of case study. The data collection techniques were carried out by interviews and documentation. After analyzing the results of interviews and searching for the documents related to recognition, depreciation, measurement, presentation and disclosure, it was found out that PT. Selaras Sejati has not fully implemented PSAK No. 16 policy well. Accounting treatment of fixed assets which were not in accordance with PSAK No. 16 was calculating the review of residual values and fixed asset useful life, and the use of the double declining balance (DDB) depreciation method. It is recommended that the company conduct an annual review of the depreciation expense on its fixed assets, using the depreciation methods which were suitable with the characteristics of its fixed assets.